Pemahaman Mahasiswa tentang Keberlanjutan dalam Kimia: Kajian Pengembangan pada Proyek Green Chemistry - Azzajjad, Muhammad Fath; Ahmar, Dewi Satria; Kilo, Ahmad Kadir (Universitas Negeri Gorontalo, 2024)
Students who have a strong understanding of concepts, good use of terminology, and the ability to invent environmentally friendly products, they can become effective drivers of change. This will enable them to support Green Chemistry innovations and practices in the future. provides practical experience to students, allows them to use the ideas they learn in real-life situations, and encourages them to show greater concern for environmental sustainability. This survey study took a sample of 28 individuals. Students' understanding of the concept of Green Chemistry is still in the